Growth and heavy metals uptake by Vicia faba in mining soil and tolerance of its symbiotic rhizobacteria - El Alaoui, Abdelkhalek; Bechtaoui, Noura; Benidire, Loubna; El Gharmali, Abdelhay; Achouak, Wafa; Daoui, Khalid; Imziln, Boujamaa; Oufdou, Khalid (Oficyna Wydawnicza Politechniki Wrocławskiej, 2019)
Faba bean plants in the 1/8 mixture with soil had the ability to accumulate Pb, Zn and Cu. 95% of the absorbed Pb were in the roots, and Cu and Zn were found in the shoots by 35% and 45%, respectively. There was a decrease in the root hairs and the number of cell layers of the root cortex alongside epidermis lesions. From the 50 tested rhizobacterial strains, 20 were able to grow at 150 mg/dm3 of Pb, 6 were resistant to 150 mg/dm3 of Zn and 8 resisted to 20 mg/dm3 of Cu. Best four strains had adsorption potentials and the biosorption was higher for Cu. These strains were capable of producing auxin and exopolysaccharides. The most tolerant strains (FD1 and FD2) isolated near the mining site produced siderophores and high amounts of exopolysaccharides. The use of such strains and V. faba could be of important biotechnological value in decreasing heavy metal pollution of mining soils.
Environment Protection Engineering. Vol. 45, 2019, nr 1, s. 83-96
Keywords: ochrona środowiska; inżynieria środowiska